2019
DOI: 10.5812/jkums.96932
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Nesfatin-1 and Insulin Resistance Changes Immediately After Circuit-Resistance Exercise and During Recovery Periods in Healthy Men

Abstract: Objectives: Resistance exercise is an effective method for weight control programs, and it might be useful to understand its influence on acute body energy hemostasis changes. Therefore, the present study aimed to examine the response of nesfatin-1 and insulin resistance (IR) to acute circuit resistance exercise and their changes during recovery periods. Methods: Twelve participants (age: 22.1 ± 2.1 y, height: 176.2 ± 6.5 cm and weight: 69.0 ± 8.2 kg) attended voluntary in this research. After performing one m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…From the 36 included studies, 23 examined humans 41–63 with 13 examining animal models 64–76 . Studies investigated the effects of chronic exercise training 41–51,63 and acute exercise 48,52–62 in humans. One study compared the effect of chronic and acute exercise 48 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…From the 36 included studies, 23 examined humans 41–63 with 13 examining animal models 64–76 . Studies investigated the effects of chronic exercise training 41–51,63 and acute exercise 48,52–62 in humans. One study compared the effect of chronic and acute exercise 48 .…”
Section: Resultsmentioning
confidence: 99%
“…The exercise session consisted of three circuits of seven exercises with 2 min and 30 s rest between circuits and exercises. The results showed that acute circuit resistance exercise increased Nesfatin‐1 62 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations